Predicting others' social interaction preferences: What to do, for how long, and how often. (February 2022) - Liu, Peggy J.; Kwon, Theresa A.
Abstract: We present a three-dimensional what, how long, and how often framework to discuss three main inferences about other people's preferences for repeated social interactions over time in terms of: (1) what to do together, (2) how long to spend together on each occasion, and (3) how often to spend time together. For each dimension, we discuss when and how people make inferences about other people's preferences, as well as the consequences of making incorrect inferences. The three dimensions are conceptually independent; however, decisions made on one dimension can sometimes affect decisions made on others. More research is needed on the interplay between multiple dimensions, including how inferences made about preferences and decisions on one dimension affect inferences about preferences and decisions on other dimensions.